Strategi Pengembangan Batik Alpukat Universitas PGRI Silampari sebagai upaya Peningkatan Penjualan - Ratih Eka Sakti; Fatma Oktarendah; Endar Pradesa (Journal of Management and Bussines (JOMB), 2024)
This research aims to explore the potential for developing Avocado Batik as an effort to diversify local avocado-based batik products. The approach used in this research is a qualitative descriptive approach, which describes the social situation being studied comprehensively, broadly and in depth. The results of the research show that the Avocado Batik MSMEs at PGRI Silampari University show a strong commitment to continuing to improve the quality of their products and services, as well as developing more effective marketing strategies to support their business growth in local and regional markets. In conclusion, this research will provide a clear picture of the potential and strategy for developing Avocado Batik as a new superior product in the Indonesian batik industry. Keywords: Avocado Batik, Increased Sales, Development Strategy